A few ideas on the relation education and communication in the field of Health - Donato, Ausonia Favorido; Rosenburg, Cornélio Pedroso (Saúde e Sociedade, 2003)
This article discusses some concepts about the link between Education and Communication in the field of Health through the discussion of two educational experiences with youngsters and adults. It begins with the circunscription of the constructed "field of health" not only as a locus from which it is possible to locate phenomena related to Health but also as a social instance and historically made by individuals who establish among themselves exchange and power relationships. Starting with the common social element, the aspects related to Education and Communication get jointed. As for Communication, we meant to approach it, not by its media dimension latu sensu but from its condition to produce a social sense in the heart of subjectivity, and to do so making use of some concepts of the Russian linguist Mikhail Bakhtin. With respect to Education it stayed out the link among the several dimensions of the process teaching-apprenticement, schematized in its fields of knowledge. At last, we could verify that, unlike an eminently communicational approach to the problems of Health, the contribution of the relation between Communication and Education, situated in the field of Health, makes one question a current tendency that privileges the media in detriment of the graduation of the subject.